PERCEPTION OF STUDENT FACULTY OF SOCIAL AND POLITICAL SCIENCEON TAGLINE - Farida Nurfalah; Mukarto Siswoyo; Heriyani Agustina (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Abstract: Given the increasing number of Private Universities (PTS), implications for competition between universities (PT) in getting prospective students. Other research method using descriptive qualitative. The results showed that 1. Characteristics of Students Fisip in this study came from various regions with the background of the school of its own country. Last Educational parents mostly high school graduate (high school). Unswagati good credibility in their eyes they are perceived only building still less orderly., 2. The Students perceptions The tagline "leading and learning base on local wisdom" is the tagline that can be recommended for use by the College, 3. The tagline "leading and learning base on local wisdom" used Unswagati shows that Unswagati very caring and upholds the will of local wisdom although implementation is still not maximized